Neither a Discipline nor a Colony: Renaissance and Re-imagination in Economic History. Issue 2 (3rd April 2017) - Ville, Simon; Wright, Claire
Abstract : After years in the wilderness, economic history is becoming fashionable once more. Intellectual shifts by its parent disciplines of history and economics, the failed experiment of economic history as a separate discipline, and the impact of major economic events have conspired to produce a renaissance in the field of study in the last decade and a half. We explain these changes and show that economic history derives its main strength from its role as an interdisciplinary research field that draws upon and integrates with its closest disciplines. We analyse the nature and recent progress of economic history in Australia and offer a prospective for its future role. Abstract :